Phenotypic Variation in an Asexual-Sexual Fish System: Visual Lateralization - Connelly, Allison D.; Ryan, Michael J. (Frontiers in Ecology and Evolution, 2021)
Sexual reproduction is nearly ubiquitous in the vertebrate world, yet its evolution and maintenance remain a conundrum due to the cost of males. Conversely, asexually reproducing species should enjoy a two-fold population increase and thus replace sexual species all else being equal, but the prevalence of asexual species is rare. However, stable coexistence between asexuals and sexuals does occur and can shed light on the mechanisms asexuals may use in order to persist in this sex-dominated world. The asexual Amazon molly (Poecilia formosa) is required to live in sympatry with one of its sexual sperm hosts –sailfin molly (Poecilia latipinna) and Atlantic molly (Poecilia mexicana)—and are ecological equivalents to their host species in nearly every way except for reproductive method. Here, we compare the visual lateralization between Amazon mollies and sailfin mollies from San Marcos, Texas. Neither Amazon mollies nor sailfin mollies exhibited a significant eye bias. Additionally, Amazon mollies exhibited similar levels of variation in visual lateralization compared to the sailfin molly. Further investigation into the source of this variation –clonal lineages or plasticity—is needed to better understand the coexistence of this asexual-sexual system.